Autologous Stem Cell Therapy for Chronic Lower Extremity Wounds: A Meta-Analysis of Randomized Controlled Trials - Kuan-Ju Chiang; Li-Cheng Chiu; Yi-No Kang; Chiehfeng Chen (Cells, 2021)
Lower extremity chronic wounds (LECWs) commonly occur in patients with diabetes mellitus (DM) and peripheral arterial disease (PAD). Autologous stem cell therapy (ASCT) has emerged as a promising alternative treatment for those who suffered from LECWs. The purpose of this study was to assess the effects of ASCT on LECWs. Two authors searched three core databases, and independently identified evidence according to predefined criteria. They also individually assessed the quality of the included randomized controlled trials (RCTs), and extracted data on complete healing rate, amputation rate, and outcomes regarding peripheral circulation. The extracted data were pooled using a random-effects model due to clinical heterogeneity among the included RCTs. A subgroup analysis was further performed according to etiology, source of stem cells, follow-up time, and cell markers. A total of 28 RCTs (n = 1096) were eligible for this study. The pooled results showed that patients receiving ASCT had significantly higher complete healing rates (risk ratio (RR) = 1.67, 95% confidence interval (CI) 1.28–2.19) as compared with those without ASCT. In the CD34+ subgroup, ASCT significantly led to a higher complete healing rate (RR = 2.70, 95% CI 1.50–4.86), but there was no significant difference in the CD34− subgroup. ASCT through intramuscular injection can significantly improve wound healing in patients with LECWs caused by either DM or critical limb ischemia. Lastly, CD34+ is an important cell marker for potential wound healing. However, more extensive scale and well-designed studies are necessary to explore the details of ASCT and chronic wound healing.